2014
DOI: 10.1111/modl.12118
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Dynamics in Language Learning: Change, Stability, and Context

Abstract: Motivation as a variable in L2 development is no longer seen as the stable individual difference factor it was once believed to be: Influenced by process‐oriented models and principles, and especially by the growing understanding of how complex dynamic systems work, researchers have been focusing increasingly on the dynamic and changeable nature of the motivation process. In this study we micro‐map the motivational dynamics of 4 language learners during their language lessons over a period of 2 weeks, using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(72 citation statements)
references
References 36 publications
4
57
0
1
Order By: Relevance
“…In particular, computer-assisted writing research suggests that certain students tend to write more when composing on computers rather than using a traditional pen-and-paper mode. A novel instrument, such as the Motometer, may be adopted by the students to record their motivation at different moments in the classroom (Waninge, Dörnyei, & de Bot, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, computer-assisted writing research suggests that certain students tend to write more when composing on computers rather than using a traditional pen-and-paper mode. A novel instrument, such as the Motometer, may be adopted by the students to record their motivation at different moments in the classroom (Waninge, Dörnyei, & de Bot, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…However, the negative effect of social milieu on her influenced her inner motivation. It was also found that even in a 45-minute lesson, motivation variability might be observed depending on types of topics taught in classroom settings and that there seem interrelated factors that explain individual and motivation variability composed of multi-layered issues (Waninge, Dörnyei, & De Bot, 2014). Motivation in a larger context such as target language country can be influenced by change, stability and context, three of which mainly constitute Complex Dynamic Systems (Larsen-Freeman & Cameron, 2008;Waninge, Dörnyei, & De Bot, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The participant undertook a test 40 minutes after the commencement of the class and commented that he had done well on the test. This explained the sudden surge in his motivation level (Waninge et al, 2014). Based on the findings of the above-mentioned research, the present study aimed to identify solutions to the problem of falling asleep in university EFL classes using a vocabulary test to motivate students.…”
Section: Literature Reviewmentioning
confidence: 93%
“…A similar study was conducted by Waninge, Dörnyei, and de Bot (2014), who examined four students' motivation over a period of two weeks. The participants, aged 11 and 12, were chosen from among students in their first year of the highest level of Dutch secondary education.…”
Section: Literature Reviewmentioning
confidence: 96%